Explaining the United States of America's Congressional Voting Variations on International Trade Organization Establishment - Giandi Kartasasmita; Andrea Prisca Kurnadi (Jurnal Ilmiah Hubungan Internasional, 2025)
This study investigates why the United States Congress produced different outcomes when consider in joining two comparable trade institutions: the International Trade Organization (ITO) in 1948 and the World Trade Organization (WTO) in 1994. Despite similar institutional settings, presidential leadership, and party platforms, Congress refused to ratify the ITO but approved the WTO. Using a paired comparative case study and structured, focused process tracing, the analysis evaluates two explanations of congressional voting behavior: the ideological alignment of members with their party’s platform and the constituency economic interests within each member’s district. The findings show that party platforms alone did not determine legislative behavior. Instead, the interaction between individual ideology and district-level economic exposure better explains cross-party defections and divergent outcomes across the two cases. Ideological divergence weakened party cohesion in both periods, but constituency economic vulnerability—particularly in import-sensitive or recession-affected regions—proved decisive in shaping opposition to trade liberalization. The study concludes that congressional responses to major trade agreements are driven less by formal party doctrine than by the economic structure of constituencies and the electoral incentives of their representatives. This highlights a persistent tension between international trade objectives and district-level economic realities in U.S. trade policymaking. Keywords: Two-level Game; Trade Institutions; Liberalization; Congressional Decision Making; Ratification.